Minimizing Responsibility: The Impact of Moral Disengagement on Cyberbullying Perpetration Among Adults - Fissel, Erica (Crime & delinquency, 2025)
Research has demonstrated a relationship between moral disengagement and cyberbullying perpetration among adolescents, indicating youth with higher levels of moral disengagement are more likely to engage in cyberbullying. Less is known, however, regarding the impact of moral disengagement, particularly the influence of the four dimensions, on adults’ involvement in cyberbullying perpetration. Using a sample of adults (n = 652; aged 18–50 years) in the United States, this study examined the relationship between the four dimensions of moral disengagement and cyberbullying perpetration. Findings revealed that approximately 12% had ever engaged in cyberbullying perpetration. Further, logistic regression results revealed that moral disengagement was a significant predictor of cyberbullying perpetration among adults, with the dimension of minimizing responsibility driving the significant relationship.